2008
DOI: 10.1042/cs20070264
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the endothelium-dependent relaxation evoked by a grape seed extract

Abstract: GSEs (grape seed extracts) which contain polyphenolic compounds cause an endothelium-dependent relaxation of blood vessels. The aim of the present study was to examine the mechanisms involved in this response. A well-characterized GSE was applied to rabbit aortic rings suspended in organ baths containing Krebs-Henseleit buffer maintained at 37 degrees C. In aortic rings pre-contacted with noradrenaline (norepinephrine), the extract produced a dose-dependent relaxation. The maximum relaxations elicited by the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 23 publications
2
77
1
1
Order By: Relevance
“…Thus, NO is involved in the in vitro vasodilator effects of red wine polyphenolic compounds (Andriambeloson, Kleschyov, Muller, Beretz, Stoclet & Andriantsitohaina, 1997;Andriambeloson, Stoclet, & Andriantsitohaina, 1999), grape seed (Edirisinghe et al, 2008;Fitzpatrick, Bing, Maggi, Fleming & O'Malley, 2002;Fitzpatrick, Fleming, Bing, Maggi & O'Malley, 2000) and grape skin extracts (Madeira et al, 2009). Regarding to grape pomace extracts, studies about their vascular effects have not been reported until now and studies concerning grape pomace extracts are limited to antioxidant (Chidambara Murthy, Singh, & Jayaprakasha, 2002) and anti-inflammatory properties associated with obesity and insulin resistance (Hogan, Canning, Sun, Sun & Zhou, 2010a;Yunoki et al, 2008).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, NO is involved in the in vitro vasodilator effects of red wine polyphenolic compounds (Andriambeloson, Kleschyov, Muller, Beretz, Stoclet & Andriantsitohaina, 1997;Andriambeloson, Stoclet, & Andriantsitohaina, 1999), grape seed (Edirisinghe et al, 2008;Fitzpatrick, Bing, Maggi, Fleming & O'Malley, 2002;Fitzpatrick, Fleming, Bing, Maggi & O'Malley, 2000) and grape skin extracts (Madeira et al, 2009). Regarding to grape pomace extracts, studies about their vascular effects have not been reported until now and studies concerning grape pomace extracts are limited to antioxidant (Chidambara Murthy, Singh, & Jayaprakasha, 2002) and anti-inflammatory properties associated with obesity and insulin resistance (Hogan, Canning, Sun, Sun & Zhou, 2010a;Yunoki et al, 2008).…”
Section: Introductionmentioning
confidence: 98%
“…In the recent years, an increasing attention has been focused on the positive effects of grape seeds extracts (Edirisinghe, Burton-Freeman, & Kappagoda, 2008) and grape skin extracts (Madeira et al, 2009) on the vascular function in isolated arteries. Grape seed extracts have also shown anti-angiogenic properties in endothelial cells (Lu, Zhang, Chen, & Wen, 2009) and protection against atherosclerosis biomarkers in vitro (Vinson, Mandarano, Shuta, Bagchi, & Bagchi, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Individually, GSE and quercetin were reported to cause an endothelium-dependent relaxation of blood vessels both in animals [Edirisinghe et al 2008;Khoo et al 2010] and in humans [Clifton, 2004;Loke et al 2008]. However, when combined, quercetin appeared to nullify the positive effect of GSE on endothelial function in high-risk subjects [Clifton, 2004].…”
Section: Therapeutic Advances In Chronic Disease 3 (2)mentioning
confidence: 99%
“…Significant reduction in BP of 11/8 mmHg (p < 0.05) were seen in another dose response study with 150 to 300 mg/d of GSE over 4 wk [306] . GSE has high phenolic content which activates the PI3K/Akt signaling pathway that phosphorylates eNOS and increases NO [306,307] .…”
Section: Additional Compoundsmentioning
confidence: 99%